A study on the effectiveness and adherence to mask mandates in stores in Greensboro, North Carolina, United States of America - Ewunkem, Akamu Jude; Barnes, Kristi Leanna (Open Science Journal, 2022)
The Governor of North Carolina requires people to wear face coverings in most public settings to curb the spread of COVID-19. Stores in Greensboro, North Carolina responded to the new executive order which strengthened the mask mandate. Every store in requires all customers to wear face masks while shopping to protect the health and safety of everyone. However, the extent to which shoppers adopted this recommendation was uncertain. The objective of this study was to determine if Greensboro shoppers adhered to the mask mandate signs in local stores. We used direct observations of shoppers (n=2,520) in stores to assess face covering use in June 2020. We found that over 25% of shoppers were seen without face masks and the odd of shoppers not wearing face masks increased significantly (P<0.05) in the evenings. A significantly (P<0.05) greater number of males (58.3%) were seen not wearing face masks than females (41.6%). The findings suggest that not all shoppers adhered to Greensboro’s Mayor, Nancy Vaughan, emergency proclamation to reinforce Governor Cooper’s Executive Order requiring face coverings in public places. This is the first direct observational study evaluating the effectiveness and the adherence to mask mandates in Greensboro, North Carolina. North Carolina is probably rated as a high risk for COVID-19 infection because there is not full compliance with the mask mandates. Future directions from this study include visiting more stores during the Spring, Summer, and Fall and examining the reasons why some individuals choose not to wear face masks in public places. Keywords: Face masks, COVID-19, Greensboro, Stores, Males, Females.